2008
DOI: 10.1111/j.1559-1816.2008.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

Affective Match in Leadership: Leader Emotional Displays, Follower Positive Affect, and Follower Performance1

Abstract: Leader emotions may play an important role in leadership effectiveness. Extending earlier research on leader emotional displays and leadership effectiveness, we propose that the affective match between follower positive affect (PA) and leaders’ emotional displays moderates the effectiveness of leader emotional displays. Leader display of emotions has more positive effects on follower behavior if the match between the valence of leader emotion and follower PA is strong rather than weak. Support for this hypothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
111
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(115 citation statements)
references
References 124 publications
2
111
0
2
Order By: Relevance
“…Furthermore, Sy et al (2005) found that groups with leaders in a positive mood exhibited better group coordination, whereas leader negative mood was related to increased group effort, both of which are outcomes that can be viewed as determinants of group performance. However, other studies failed to establish a direct effect between leader emotional displays and work performance, both on the individual (Damen, van Knippenberg, & van Knippenberg, 2008;Van Kleef, Homan, Beersma, & van Knippenberg, 2010;Venus, Stam, & van Knippenberg, 2013) and group level (Seong & Choi, 2014).…”
Section: Main Effects On Work-related Behaviourmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, Sy et al (2005) found that groups with leaders in a positive mood exhibited better group coordination, whereas leader negative mood was related to increased group effort, both of which are outcomes that can be viewed as determinants of group performance. However, other studies failed to establish a direct effect between leader emotional displays and work performance, both on the individual (Damen, van Knippenberg, & van Knippenberg, 2008;Van Kleef, Homan, Beersma, & van Knippenberg, 2010;Venus, Stam, & van Knippenberg, 2013) and group level (Seong & Choi, 2014).…”
Section: Main Effects On Work-related Behaviourmentioning
confidence: 99%
“…Second, compared to a mismatch, a match between leader emotional expressions and follower trait affect is proposed to result in increased leadership effectiveness (Damen, van Knippenberg, & van Knippenberg, 2008). The CIM's propositions describing a match or mismatch situation could be interpreted as a line of argumentation to the end of exploring the effects of consistency versus inconsistency between various leader and follower variables.…”
Section: Underlying Mechanisms and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers have found that leaders who express positive affect are rated more favorably than leaders who express negative affect (Barsade & Gibson, 2007;Bono & Illies, 2006;Dasborough and Ashkanasy, 2002) and that these favorable ratings are a result of emotional contagion (Barsade & Gibson, 2007;Bono & Illies, 2006;Damen, Van Knippenberg, & Van Knippenberg, 2008). According to these researchers, leaders' positive affect arouses positive emotion in followers, which in turn results in positive mood.…”
Section: Charismatic Rhetoric and Affective Languagementioning
confidence: 99%
“…Despite the increasing research interest that in recent times has concerned the positive emotions involved in the leadership processes (see e.g . [3,5,6,7], the examin at ion of the ro le o f pos it ive other-directed emotions involved in the leader-fo llo wer relationship has been undeservedly neglected. Especially, if some exceptions are related to the study of empathy (8), gratitude [9], and moral elevation [10], there is a nearly complete lack of research concerning leadership and admiration.…”
Section: Introductionmentioning
confidence: 99%